Một số vấn đề về văn hoá tổ chức trong trường đại học - Nguyễn , Việt Hồng; Nguyễn , Lộc (Tạp chí Giáo dục, 2022)
Organizational culture in universities is a new concept in educational management yet has attracted much attention from local and international researchers. Researchers have shown that this is one of the tools for effective management to orient toward success and increase the operational efficiency of organizations in general and university organizations in particular. On the basis of research on the concept, characteristics and functions of organizational culture in universities, the article proposes 8 steps to develop organizational culture of universities today for the purpose of creating motivation for development, reducing conflicts and improving the quality of educational activities in the university. This study contributes to supplementing and clarifying some theoretical issues about traditional culture in universities; meanwhile, suggesting steps to develop organisational culture in universities to help managers make appropriate policies to improve training quality, international integration capacity and enhance institutional competitiveness.